Integrated workflow for a semi-automated and robotic facade renovation - Iturralde, Kepa; Shen, Wenlan; Bazan, Renzo; Amo-Grau, Oscar; Liu, Danya; Srinivasaragavan, Aravind; Das, Samanti; Bock, Thomas; Holst, Christoph (Frontiers in Built Environment, 2025)
The drive towards enhanced efficiency, precision, and automation in the realm of building façade renovation is a salient factor in this paradigm shift. This transition is characterized by the need for streamlined processes that encompass design, fabrication, and installation. This paper expounds upon an integrated workflow that combines data acquisition, geometric modeling, and robotic assembly to automate the manufacturing of prefabricated facade modules for building renovation. The workflow consists of several steps. First, a structured online data acquisition platform has been developed to standardize the digital modeling process, providing users with a guided approach from basic project input to BIM (Building Information Modeling) -compatible outputs. Next, to enhance the precision of facade modeling from the previous step, a geometry estimation method based on AprilTag is utilized. This method facilitates sub-millimeter accuracy through photogrammetric calibration and plane fitting. These geometric definitions are subsequently transferred to a CAM (computer-assisted manufacturing) pipeline, which enables automated detailing and fabrication of panels using industry-standard software. The final step involves robotic assembly driven by a robotic manipulator with a vision-assisted system for flexible pick-and-place operations. The system demonstrated sub-centimeter assembly precision and reduced manual layout and clash-checking time in different case studies. The proposed system offers a scalable and precise solution for energy-efficient building renovation through a seamless connection between digital modeling and robotic execution.